(untitled) (Social and Environmental Law Journal, 2024)
This research analyzed the relationship between the actions of rural social movements, especially the actions of members of the Landless Rural Workers Movement (MST), and the process of criminalization of their conduct by legal operators, whose vector is linked the influences and reinterpretations of a positivist criminological perspective and social reaction. To this end, this study proposed to scientifically verify how criminal knowledge can be a legitimate instrument to promote the criminalization and criminal stigmatization of these workers. It was demonstrated from the analysis of duly selected concrete cases how the process of criminalization of landless rural workers develops through the use of criminological discourse as an instrument for manipulating social reality. Given the social and political configuration of the object of study, characterized by the movement of ideas and the various interest groups that make up the context of the Brazilian countryside and access to agrarian policies, especially access to and democratization of land, the theoretical categories of analysis scientific aspects covered by the historical-dialectic framework were essential for the purposes of the proposed research.